2021
DOI: 10.1161/circulationaha.121.055525
|View full text |Cite
|
Sign up to set email alerts
|

No-Touch Versus Conventional Vein Harvesting Techniques at 12 Months After Coronary Artery Bypass Grafting Surgery: Multicenter Randomized, Controlled Trial

Abstract: Background: Vein graft occlusion is deemed a major challenge in coronary artery bypass grafting. Previous studies implied that the no-touch technique for vein graft harvesting could reduce occlusion rate compared with the conventional approach; however, evidence on the clinical benefit and generalizability of the no-touch technique is scare. Methods: From April 2017 to June 2019, we randomly assigned 2655 patients undergoing coronary artery bypass graft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
64
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(70 citation statements)
references
References 45 publications
(89 reference statements)
6
64
0
Order By: Relevance
“…Both covariates were omitted from the propensity score model as they have been reported to be affected by the treatment of interest in previous randomized controlled trials. 14,15,27 Propensity score matching resulted in 923 pairs of C-SVG and NT-SVG patients. Baseline characteristics of the propensity matched cohorts were almost identical.…”
Section: Baseline Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both covariates were omitted from the propensity score model as they have been reported to be affected by the treatment of interest in previous randomized controlled trials. 14,15,27 Propensity score matching resulted in 923 pairs of C-SVG and NT-SVG patients. Baseline characteristics of the propensity matched cohorts were almost identical.…”
Section: Baseline Characteristicsmentioning
confidence: 99%
“…2,4,5,7,12,13 Data from 2 recent multicenter randomized controlled trials provide conflicting evidence regarding the proposed superior longevity of NT-SVGs. 14,15 Results from the ongoing SWEDEGRAFT multicenter randomized controlled trial are pending. 16 It is important to consider that SVG failure may not represent a valid surrogate for clinical outcome after CABG, as the impact of SVG failure on clinical outcome remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Initially there appeared little acceptance for this technique with it being used solely in the department of thoracic and cardiac surgery at Örebro University Hospital, where it was developed. Following publication of both the randomized clinical trials and the basic science studies, considerable interest has been raised worldwide whereby the NT technique is recognized and has been adopted in many countries, especially in Sweden [ 12 , 13 ] ), Japan [ 14 ] , China [ 15 ] , and South Korea [ 16 ] . Currently, two large randomized multicenter trials are ongoing to evaluate the NT technique.…”
mentioning
confidence: 99%
“…Currently, two large randomized multicenter trials are ongoing to evaluate the NT technique. The first one is being performed in China, which included 2,655 patients and the one-year results was recently published [ 15 ] . The second similar ongoing randomized trial is in Sweden and 900 patients were included [ 13 ] .…”
mentioning
confidence: 99%
“…However, as surgical and adjunctive medical therapies continue to improve, so do the outcomes of saphenous conduit. For example, in the recent Graft Patency Between no-touch Vein Harvesting Technique and Conventional Approach in Coronary Artery Bypass Graft Surgery (PATENCY) trial, Tian and colleagues 2 demonstrated early SVG failure rates of 2.8% with no-touch SVG harvest and 4.8% ( P < .001) with conventional SVG harvesting. At 1 year, graft patency was 94.3% in the no-touch SVG group and 93.5% in the conventional harvest group ( P < .001).…”
mentioning
confidence: 99%